Analysis Of Business Feasibility Study On The Development Of Father Yulianto's Tofu And Tempe Msme Business Reviewed From The Production And Marketing Aspects - Septi, Septi; Febliansa, Rahman; Monique D, Eska Prima (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This research aims to evaluate the feasibility of Pak Yulianto's tofu and tempeh factory business in terms of marketing and production. This feasibility analysis uses market and competition analysis. The results show that Pak Yulianto's tofu and tempe business from the production aspect is declared feasible because the business location is strategic and easy to reach for consumers and the production process is easy. Meanwhile, the results of the research from the marketing aspect stated that it was worthy of a quality product because it used quality raw materials, and the price was affordable so that all groups could buy it and the promotion that the owner gave was enough to make consumers aware of the product he was selling.